TINJAUAN LITERATUR: BIOAKUMULASI LOGAM BERAT PADA IKAN DI PERAIRAN INDONESIA - Said Ali Akbar; Hanis Kusumawati Rahayu (UIN AR-RANIRY, 2023)
Heavy metals are frequently employed in a variety of industries, including industry, agriculture, food processing, and domestic appliances. Heavy metal concentrations will be extremely high in locations with residential, mining, and manufacturing activity. The concentration of heavy metals in fish reflects the state of heavy metal pollution in the ecosystem. Heavy metal accumulation in aquatic creatures' organs can occasionally exceed the level of heavy metals in their environment. The purpose of this literature review is to give information on the bioaccumulation of heavy metals in fish in Indonesian seas. 38 fish species were recorded, and literacy parameters in the form of sample locations and levels, units and types of heavy metals discovered were summarized. Pb > Cd > Hg > Cu > As > Zn > Cr > Mn > Fe is the order of metal abundance discovered. It is advised that heavy metal contamination studies be carried out in the future as part of the government's strategy for tracking down this problem.